Challenge and opportunity for the millennial school counselor - Suryahadikusumah, Ahmad Rofi; Kurniasari, Kurniasari (Konselor, 2020)
This research is based on millennial performance needs in guidance and counseling services in Palembang. Millennial is a dynamic generation and skilled in technology, but also afraid of loyalty and commitment. Also, millennial school counselors are expected to be able to overcome the gap between the majority of school counselors who belong to Gen X by the way students as generation z solve problems. Therefore, swot analysis is important to obtain an overview of the opportunities and challenges of millennial school counselors that will be the basis for the development of the counseling profession in the current era. Research using survey methods. Surveys are used to obtain an accurate and clear picture of the strengths and weaknesses shown by the millennium, as a basis for mapping challenges and opportunities. The results found that the challenge of millennial school counselors was in the use of technology, and they had the opportunity to develop professionalism consistently. Study recommendations for optimizing the strength of Millennial school counselors are 1) maximizing digital literacy, 2) using design thinking in innovation, 3) Habits as consumers must be changed with more critical and creative application of process technology.